The ways to improve the facade architecture of 1970s typical residential buildings - Melnikova, Irina; Roshchin, Maxim (project baikal, 2024)
A significant part of the 1970s housing stock of large cities of the Russian Federation is in need of renovation. However, there is no renovation programme for the 9-storey panel housing stock, unlike the 5-storey housing stock, which is now being developed in Moscow. It is proposed to solve the problem of modernisation of facades of typical residential buildings without resettlement of tenants by minimal architectural means, which can contribute to the formation of a favourable modern urban environment in these old quarters. Possible solutions are offered on the basis of modern and historical world experience in panel house-building.
Keywords: modernisation; standard housing; large-panel facades; facade proportions; balconies; window openings